2020
DOI: 10.1021/acssuschemeng.0c04163
|View full text |Cite
|
Sign up to set email alerts
|

Upcycling Poultry Feathers with (Nano)cellulose: Sustainable Composites Derived from Nonwoven Whole Feather Preforms

Abstract: Poultry feathers are low cost, abundant bioderived materials that are often regarded as waste. In this work, we report a simple method akin to papermaking to upcycle whole poultry feather waste into nonwoven whole feather preforms. This was achieved by utilizing (nano)cellulose fibers, namely, wood pulp and nanocellulose, as binders. It was found that the hornification between adjacent (nano)cellulose fibers trapped and held the whole poultry feathers together, producing a rigid and robust nonwoven whole feath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
(34 reference statements)
0
11
0
Order By: Relevance
“…The high surface area of nanocellulose leads to large number of contact points between adjacent fibres, which in turn gives rise to cellulose nanopaper with superior mechanical properties over conventional paper (Mao et al, 2017;Kontturi et al, 2021) that can be used as two-dimensional reinforcement for polymers (Santmarti et al, 2019;Santmarti et al, 2020). The high surface area of nanocellulose also leads to higher coverage of micrometre-sized natural or waste fibres, binding them into robust and rigid fibreboards (Lee et al, 2014b;Fortea-Verdejo et al, 2016;Vilchez et al, 2020). Therefore, the reliable characterisation of the surface area of nanocellulose is important for the future development of nanocellulose-based advanced materials.…”
Section: Introductionmentioning
confidence: 99%
“…The high surface area of nanocellulose leads to large number of contact points between adjacent fibres, which in turn gives rise to cellulose nanopaper with superior mechanical properties over conventional paper (Mao et al, 2017;Kontturi et al, 2021) that can be used as two-dimensional reinforcement for polymers (Santmarti et al, 2019;Santmarti et al, 2020). The high surface area of nanocellulose also leads to higher coverage of micrometre-sized natural or waste fibres, binding them into robust and rigid fibreboards (Lee et al, 2014b;Fortea-Verdejo et al, 2016;Vilchez et al, 2020). Therefore, the reliable characterisation of the surface area of nanocellulose is important for the future development of nanocellulose-based advanced materials.…”
Section: Introductionmentioning
confidence: 99%
“…As CNFs are input, the breakage of BF/CNFs is converted from BF-oriented brittle fracture behavior to elastic and progressive failure due to the energy dissipation effect of the CNF bundle. Vilchez prepared chicken hair fiber/CNF preforms and confirmed that as the quantity of CNFs enlarged, progressive failure appeared, increasing tensile elongation [ 18 ]. This progressive failure behavior of the BF/CNFs by CNFs consequently contributed to a substantial surge in the BF/CNF preform toughness.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanical properties of poly AESO/sisal preforms manufactured by thermal curing following vacuum-assisted resin injection are also extensively improved. It is known that the excellent binding and adhesion ability of these nanocelluloses can be clearly expressed in natural fibers, including sisal and silk fibers [ 17 , 18 ]. However, most of the research results indicate that bacterial cellulose was used as a binder [ 19 ], and there has been no effort to manufacture a hierarchical fibrous-composite preform using microfibers and nanocellulose produced from the same tree species.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms of degradation are not fully known [27,[29][30][31]. One of the initial theories was presented by Raubitschek [32], but this was discarded after the discovery of keratinase [33,34]. Other theories pointed to, inter alia, enzymatic keratin digestion by keratinolytic enzymes and the sulphuric amino acid metabolism of microorganisms as the basis of decomposition [35][36][37].…”
Section: Discussionmentioning
confidence: 99%